The Role of Prudence in Moderating the Effect of Bonus Mechanism, Intangible Assets, and Inventory Intensity Ratio on Transfer Pricing - Uswatun Khasanah; Trisni Suryarini (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
This study aims to examine prudence's role in moderating the effect of bonus mechanism, intangible asset, and inventory intensity ratio on transfer pricing decisions. This research population is all property, real estate & construction companies, and manufacturing companies listed on the Indonesia Stock Exchange in 2018. The sampling technique uses a purposive sampling method to obtain 109 units of analysis. This study uses moderated regression analysis (MRA), which is processed using IBM SPSS 21. This study proves that the bonus mechanism does not affect, while intangible assets and inventory intensity ratio significantly affect transfer pricing decisions. Prudence is proven to moderate the intangible assets' influence but does not moderate the impact of the bonus mechanism and inventory intensity ratio on transfer pricing decisions. This study concludes that the bonus mechanism does not affect the transfer pricing decision. Prudence is proven to moderate the effect of intangible assets but does not moderate the impact of the bonus mechanism and inventory intensity ratio on transfer pricing decisions.